2006
DOI: 10.3748/wjg.v12.i37.5978
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacilli, bifidobacteriaandE. colinissle induce pro- and anti-inflammatory cytokines in peripheral blood mononuclear cells

Abstract: The incubation of probiotic strains, which have been used in clinical trials for inflammatory diseases, with immunocompetent cells leads to different species specific reactions. High IL-10 response to cell debris of bifidobacteria and E. coli nissle can be found. This corresponds to positive effects of bifidobacteria and E. coli nissle in clinical trials for inflammatory bowel disease compared to negative outcomes obtained with lactobacilli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
0
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 41 publications
6
73
0
7
Order By: Relevance
“…Our data is consistent with previous studies in which bifidobacteria were shown to induce higher IL-10 production as compared to lactobacilli [9,16] . The antiinflammatory actions of IL-10 could be helpful in the treatment of inflammatory conditions or diseases.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our data is consistent with previous studies in which bifidobacteria were shown to induce higher IL-10 production as compared to lactobacilli [9,16] . The antiinflammatory actions of IL-10 could be helpful in the treatment of inflammatory conditions or diseases.…”
Section: Discussionsupporting
confidence: 93%
“…However, there is only limited amount of comparative data on the immunomodulatory properties of several different probiotic bacterial strains within the same experimental system. Published data is mainly limited to the analysis of the effects of Lactobacillus and Bifidobacterium genera [9,[11][12][13]44] . In the present study combinations of different grampositive probiotic bacteria did not induce any additive or synergistic cytokine production in PBMCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various experiments indicate that the ability to induce the secretion of various cytokines is mediated to a large extent by cell wall components. 177,179,180 In particular, peptidoglycans have been implicated in IL-12 induction in splenocytes, 178 while lipoteichoic acids are involved in the stimulation of TNF-α production in macrophages and splenocytes. 181 In addition, DNA has been shown to mediate a variety of immunomodulatory effects of certain probiotic strains both in vitro and in vivo.…”
Section: Identifi Cation Of Active Probiotics Components and Receptormentioning
confidence: 99%